Surveillance-activated defenses block the ROS-induced mitochondrial unfolded protein response. - Eva D Runkel; Shu Liu; Ralf Baumeister; Ekkehard Schulze (PLoS Genetics, 2013)
Disturbance of cellular functions results in the activation of stress-signaling pathways that aim at restoring homeostasis. We performed a genome-wide screen to identify components of the signal transduction of the mitochondrial unfolded protein response (UPR(mt)) to a nuclear chaperone promoter. We used the ROS generating complex I inhibitor paraquat to induce the UPR(mt), and we employed RNAi exposure post-embryonically to allow testing genes whose knockdown results in embryonic lethality. We identified 54 novel regulators of the ROS-induced UPR(mt). Activation of the UPR(mt), but not of other stress-signaling pathways, failed when homeostasis of basic cellular mechanisms such as translation and protein transport were impaired. These mechanisms are monitored by a recently discovered surveillance system that interprets interruption of these processes as pathogen attack and depends on signaling through the JNK-like MAP-kinase KGB-1. Mutation of kgb-1 abrogated the inhibition of ROS-induced UPR(mt), suggesting that surveillance-activated defenses specifically inhibit the UPR(mt) but do not compromise activation of the heat shock response, the UPR of the endoplasmic reticulum, or the SKN-1/Nrf2 mediated response to cytosolic stress. In addition, we identified PIFK-1, the orthologue of the Drosophila PI 4-kinase four wheel drive (FWD), and found that it is the only known factor so far that is essential for the unfolded protein responses of both mitochondria and endoplasmic reticulum. This suggests that both UPRs may share a common membrane associated mechanism.